The Relationship Between Academic Encouragement and Academic Self-Efficacy: A Moderated Mediation Model - Gong, Zhun; Jiao, Xinian; Xia, Xinlei; Yu, Haixin; Lv, Cixian (Frontiers in Psychology, 2022)
To explore the influence mechanism and boundary conditions of academic encouragement on college students’ academic self-efficacy, this study did a questionnaire survey and used the four scales, namely, Academic Encouragement Scale (AES), Course Subscale of the College Self-Efficacy Inventory (CCSI), Adult Hope Scale (AHS), and Campus Connectedness Scale (CCS). The questionnaires were distributed both online and offline. A total of 355 questionnaires were distributed, with 267 valid returns. Among them, 139 were women (52.1%) and 128 were men (47.9%), and the age range is 18–24 years old. As for the grade level, 123 were first-year college students (46.1%), 58 were second-year college students (21.7%), and 86 were third-year college students (32.2%). The results of this study showed the following. (1) Campus connectedness or hope mediated the relations between (challenge-focused or potential-focused) encouragement and academic self-efficacy. (2) Academic engagement could not moderate the above mediation models.